Strategi Pengelolaan Zakat, Infaq dan Sedekah (ZIS) Terhadap Pemberdayaan Ekonomi Umat Dalam Pencapaian Sustainable Development Goals (SDGs) Pada Masa Covid-19 - Khavid Normasyhuri; Budimansyah Budimansyah; Ekid Rohadi (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study was to determine the management and strategy for the management of Zakat, Infaq and Sedekah (ZIS) at the Nurul Iman Institute of Zakat, Infaq and Sedekah (ZIS) (LAZIS) in Lampung Province towards the economic empowerment of the people, especially in achieving the first program of Sustainable Development Goals (SDGs), namely poverty in rural areas. the time of the covid-19 pandemic. The method used is qualitative with a field research approach and is descriptive analysis. The research was conducted at the Nurul Iman Zakat, Infaq and Sedekah (ZIS) Institute (LAZIS) in Lampung Province. The results of the study indicate that the process of managing, distributing and utilizing Zakat, Infaq and Sedekah (ZIS) carried out by the Nurul Iman Institute of Zakat, Infaq and Sedekah (ZIS) (LAZIS) of Lampung Province from the stage of collecting Zakat, Infaq and Sedekah (ZIS) has been very effective with taking advantage of current digitalization, even the amount of zakat that has been collected continues to increase from year to year. Then Zakat, Infaq and Sedekah (ZIS) are very good because they choose which zakat is consumptive and productive so that the zakat funds distributed can be efficient and effective. Then the utilization of Zakat, Infaq and Sedekah (ZIS) is very appropriate where the productive zakat given makes zakat funds as capital for Small and Medium Enterprise (SME) with the aim of encouraging mustahiq (zakat recipients) to be able to have independent businesses in changing their living conditions in Indonesia. the current covid-19 period. Then the management strategy of Zakat, Infaq and Sedekah (ZIS) through the development and capital assistance of Small and Medium Enterprise (SME) has been very good with indicators of changes or increases in income from mustahiq who receive productive zakat funds.